2021
DOI: 10.3389/fphar.2021.622744
|View full text |Cite
|
Sign up to set email alerts
|

Pure Total Flavonoids From Citrus Protect Against Nonsteroidal Anti-inflammatory Drug-Induced Small Intestine Injury by Promoting Autophagy in vivo and in vitro

Abstract: Small intestine injury is an adverse effect of non-steroidal anti-inflammatory drugs (NSAIDs) that urgently needs to be addressed for their safe application. Although pure total flavonoids from citrus (PTFC) have been marketed for the treatment of digestive diseases, their effects on small intestine injury and the underlying mechanism of action remain unknown. This study aimed to investigate the potential role of autophagy in the mechanism of NSAID (diclofenac)-induced intestinal injury in vivo and in vitro an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Now, diclofenac is one of the most prescribed drugs worldwide, and it is also one of the commonly used modeling drugs for NSAID-related enteropathy. In a diclofenac-induced rat model, intestinal tissue mucosal congestion, edema, erosion, and even ulceration could be observed ( Chen et al, 2021 ). The intestinal injury was evaluated in ulceration, adhesion to the surrounding tissue, and diarrhea using the Reuter BK scoring method.…”
Section: Models Of Nsaids Induced Small Intestinal Inflammationmentioning
confidence: 99%
See 2 more Smart Citations
“…Now, diclofenac is one of the most prescribed drugs worldwide, and it is also one of the commonly used modeling drugs for NSAID-related enteropathy. In a diclofenac-induced rat model, intestinal tissue mucosal congestion, edema, erosion, and even ulceration could be observed ( Chen et al, 2021 ). The intestinal injury was evaluated in ulceration, adhesion to the surrounding tissue, and diarrhea using the Reuter BK scoring method.…”
Section: Models Of Nsaids Induced Small Intestinal Inflammationmentioning
confidence: 99%
“…NSAID-induced autophagy inhibition impaired the integrity of the mucus layer combined with the inability of intestinal epithelial cells to clear intracellular pathogens, which elicited an uncontrolled inflammatory response eventually ( Chamoun-Emanuelli et al, 2019 ). Pure total flavonoids from citrus could promote autophagy to protect the small intestinal barrier by activating the PI3K/Akt signaling pathway ( Chen et al, 2021 ). It is a flavonoid isolated and purified from citrus peel, and its medicinal value for gastrointestinal protection has been demonstrated.…”
Section: Factors Involved In the Pathogenesis Of The Nsaid-associated...mentioning
confidence: 99%
See 1 more Smart Citation
“…Reasonable intervention of intestinal microenvironment is of great significance to guide rational drug use in clinic. ( Chen et al, 2014 ; Chen et al, 2021 ) studied the mechanism of small intestinal side reactions induced by non-steroidal antiinflammatory drugs (NSAIDs) in vivo , concluded that the integrity of intestinal barrier of the mice would be protected after treating with PTFC. Authors induced intestinal injury in SD rats via continuous irrigation stomach with diclofenac (7.5 mg/kg).…”
Section: Pharmacological Effectsmentioning
confidence: 99%
“…Merr . (PTFC) were found, including naringin, neohesperidin, narirutin, and hesperidin, and the content were 243.78 ± 2.69, 5.96 ± 0.06, 12.11 ± 0.12, and 136.04 ± 4.24 mg/g, respectively ( 9 ). Since PTFC is regarded as the major active ingredient of C. maxima (Burm.)…”
Section: Introductionmentioning
confidence: 99%